(3SjQI EeGe GdgOi hGdUOb CejQ GdeDefjf GdgGOj Edi GdMb jMji Hf GdMSjf Hf GdbGSe Hf EHQGgje Hf ESeGYjd Hf EHQGgje Hf GdMSf Hf GdMSf Hf Ydj Hf CHj WGdH hGHf aGWeI GdRgQGA GHfI QShd Gddg Udi Gddg Ydjg hSde hYdi Bdg GdWGgQjfs - (3Gdchaj, eMeO Hf ESeGYjds
(3ChdgG (B:s
(3GdMeO ddg aeG cGf Pdc YdefG Cf GdLgGO eY ef bGe ef GdCFeI ef hdO GdMSf hGdMSjf YdjgeG GdSdGe ef CcHQ GdaQGFV GdJj aQVgG Gddg Ydi YHGOg hChLH def bGe HgG KhGHg s
(3BNQgG (B:s
(3QLY GdMOjK hhbY Hjf GdbGSe Hf CMeO hHjf CMeO Hf eMeO GdVMGc GNJdGa heHGYOI MJi NQL GdbGSe aj MRHg ade JZfg GdYTjQI hcSQJ Ydjg hGfgReJ Yfg aYGO Edi RHjOI Je GdcJGHs
(3HhSe (B: (3eMeO Ydj GdgGOjs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJGQjNs